Chapter 12 Content-as-Practice Studying Digital Content with a Media Practice Approach - Bareither, Christoph (Taylor & Francis, 2023)
At the heart of many studies in media anthropology is an interest in media practices. While practice-oriented approaches have gained momentum as of late, there has been little discussion about how they can include particular "media texts" or "media content" into their research designs. This is especially true for digital content on social media platforms, such as digital images, captions, emojis, hashtags, and so on, which have become popular objects of ethnographic investigation. Though digital content has clear empirical value for ethnographic studies, researchers are unclear about how to approach it conceptually and methodologically. In the following chapter, I argue that digital content itself can be analysed as practice. Using my ethnographic study of digital practices at the Memorial to the Murdered Jews of Europe as an example, I show that digital content can be studied as routines in the interplay of human bodies, social and cultural conventions, and the affordances of digital media technologies. My practice approach does not read content as text; rather, it asks how the practices of its creators live on through digital content. This perspective offers a new way of conducting content analysis from an ethnographic perspective and expands the toolbox available for media anthropological research.